Novel dry electrode binder and preparation method thereof, dry electrode sheet
By using polyethylene glycol-maleate and/or its copolymer as dry electrode adhesives, the low adhesion and environmental protection problems of PTFE in the field of lithium batteries are solved, and higher adhesion and conductivity are achieved, and the performance and production efficiency of the battery are improved.
Patent Information
- Application Number
- CN202411924825.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing polytetrafluoroethylene (PTFE) as a dry electrode adhesive has low adhesion, environmental protection problems and high processing requirements, which limits its wide application in the field of lithium batteries.
Polyethylene glycol-maleate and/or its copolymer are used as the new dry electrode binder, and the adhesion and conductivity with the electrode active material are improved through esterification reaction and copolymerization.
It significantly enhances the adhesion to the electrode active material, improves the cycle stability and capacity retention of the battery, reduces material cost and production complexity, and has good environmental protection performance.
Smart Images

Figure SMS_9 
Figure SMS_10 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy batteries, and in particular to a novel dry-process electrode binder and a preparation method thereof, and a dry-process electrode pole piece. Background Art
[0002] In the manufacturing process of lithium-ion batteries, the traditional wet electrode preparation process has always dominated. This method dissolves the active material, conductive agent and binder in a solvent to make a uniform slurry, which is then coated on the metal current collector. After drying and compaction, the electrode is finally obtained. However, the limitations of the use of the wet process are becoming increasingly apparent, especially in terms of environmental protection and production costs. Commonly used solvents such as NMP (N-methylpyrrolidone), although with good solubility, have volatility and toxicity problems, posing potential hazards to workers' health and the environment. In addition, the steps of the wet process are cumbersome, especially the drying process, which not only consumes a lot of energy, but also prolongs the production cycle, increases the complexity of the process and the maintenance cost of the equipment. Therefore, environmentally friendly and low-cost production methods have become the research direction, and dry electrode preparation technology has emerged.
[0003] The core of dry electrode preparation technology is to eliminate the use of organic solvents, avoiding solvent contamination and complex solvent recovery problems in wet processes. In the early exploration of this technology, researchers tried to use solid binders, such as polytetrafluoroethylene (PTFE), which is an ideal choice due to its excellent chemical stability and mechanical properties. By directly mixing PTFE powder with active materials and applying high temperature and pressure, these materials can be effectively tightly combined into electrode membranes. Compared with the wet process, a significant advantage of the dry process is that it greatly simplifies the production process, reduces energy consumption and waste gas emissions. At the same time, the dry process has gradually explored other binder materials, such as hot melt adhesives. These binders become fluid when heated and can be mixed with active materials to form a stable electrode structure after cooling. Although the use of such binders needs to consider their temperature resistance and chemical stability, they provide an effective solution and further promote the application of dry processes in lithium battery production.
[0004] Polytetrafluoroethylene (PTFE) has certain advantages in the preparation of lithium battery electrodes, but its fluorine characteristics also bring challenges to its application. Due to its fluorinated structure, PTFE has excellent chemical stability and high temperature resistance, but it also leads to some disadvantages.
[0005] First of all, the fluorine-containing properties of PTFE make it environmentally friendly. The strong chemical inertness of fluorine makes it difficult to react effectively with many materials, limiting its synergistic effect with other functional materials or binders. This characteristic makes the adhesion between PTFE and electrode materials weak, especially during multiple charge and discharge processes, the active materials are prone to fall off or separate, reducing the cycle performance and capacity retention of the battery. In addition, the high fluorine content of PTFE may cause it to release harmful gases in some environments. At high temperatures or under certain conditions, fluorides may volatilize or react with other substances, causing environmental pollution or corrosive effects on equipment, especially during the production process, which requires higher requirements for process environment and waste gas treatment. This increases the complexity and cost of production, especially in terms of controlling emissions and solvent recovery.
[0006] The fluorinated nature of PTFE also makes it highly electrically insulating, limiting its use in electrodes, especially in areas where conductivity is required. In addition, since PTFE itself does not have electronic conductivity, a large amount of conductive agents (such as carbon black or carbon nanotubes) must be added, further increasing material costs and potentially affecting the conductivity efficiency of the electrode.
[0007] In summary, although PTFE performs well in chemical stability, high temperature resistance and corrosion resistance, its low adhesion, environmental issues and high processing requirements caused by its fluorine-containing nature limit its widespread application in the field of lithium batteries. Summary of the invention
[0008] The technical problem to be solved by the embodiments of the present invention is to provide a new dry electrode binder and a preparation method thereof, and a dry electrode pole piece, so as to overcome the limitations of the existing polytetrafluoroethylene (PTFE) as a dry electrode binder, thereby improving the preparation process of battery electrodes and the performance of batteries.
[0009] In order to solve the above technical problems, an embodiment of the present invention proposes a novel dry electrode binder, including polyethylene glycol-maleate.
[0010] Accordingly, an embodiment of the present invention further provides a method for preparing a novel dry electrode binder, comprising:
[0011] Dissolution step: Take appropriate amounts of polyethylene glycol and maleic anhydride in molar ratio, and then add a solvent to completely dissolve the polyethylene glycol and maleic anhydride to obtain a uniform solution;
[0012] Esterification reaction steps: adding an appropriate amount of catalyst and stirring evenly to carry out esterification reaction, and adding an appropriate amount of dehydrating agent to absorb the water generated by the esterification reaction;
[0013] Solvent evaporation and concentration step: removing the reaction solvent to obtain a concentrated product;
[0014] Purification step: The concentrated product is subjected to solvent recrystallization to obtain pure polyethylene glycol-maleate, and then filtered, separated, and dried to obtain pure polyethylene glycol-maleate as a novel dry electrode binder.
[0015] Furthermore, the solvent in the dissolving step is anhydrous xylene or dichloromethane.
[0016] Furthermore, in the esterification step, the temperature is maintained at 100-130°C during the esterification reaction.
[0017] Accordingly, an embodiment of the present invention further provides a novel dry electrode binder, comprising a polyethylene glycol-maleate-polypyrrole copolymer, wherein the chemical formula of the polyethylene glycol-maleate-polypyrrole copolymer is:
[0018] ;
[0019] Wherein, m and n are both positive integers.
[0020] Accordingly, an embodiment of the present invention further provides a method for preparing a novel dry electrode binder, comprising:
[0021] Dissolution step: Take appropriate amounts of polyethylene glycol and maleic anhydride in molar ratio, and then add a solvent to completely dissolve the polyethylene glycol and maleic anhydride to obtain a uniform solution;
[0022] Esterification reaction steps: adding an appropriate amount of catalyst and stirring evenly to carry out esterification reaction, and adding an appropriate amount of dehydrating agent to absorb the water generated by the esterification reaction;
[0023] Solvent evaporation and concentration step: removing the reaction solvent to obtain a concentrated product;
[0024] Purification step: the concentrated product is subjected to solvent recrystallization to obtain polyethylene glycol-maleate;
[0025] A polymerization reaction step: mixing polyethylene glycol-maleate with pyrrole to obtain a mixed solution;
[0026] Add ammonium persulfate solution dropwise to allow ammonium persulfate to gradually polymerize with pyrrole, and collect the resulting precipitate;
[0027] The unreacted pyrrole monomer and residual ammonium persulfate are removed by washing, and the polyethylene glycol-maleate-polypyrrole copolymer is obtained by drying to serve as a novel dry electrode binder.
[0028] Furthermore, in the polymerization step, deionized water is first used for washing until the filtrate is neutral; and then anhydrous ethanol is used for washing.
[0029] Furthermore, in the polymerization step, the temperature is maintained at 0°C-5°C during the mixing and polymerization process.
[0030] Furthermore, in the esterification reaction step, the added catalyst is toluenesulfonic acid.
[0031] Accordingly, an embodiment of the present invention further provides a dry electrode plate, comprising polyethylene glycol-maleate and / or polyethylene glycol-maleate-polypyrrole copolymer, wherein the copolymerization chemical formula of the polyethylene glycol-maleate-polypyrrole copolymer is:
[0032] ;
[0033] Wherein, m and n are both positive integers.
[0034] The beneficial effects of the present invention are as follows: the copolymerized and modified polyethylene glycol-maleate of the present invention has several significant advantages as a dry electrode binder compared to traditional polytetrafluoroethylene (PTFE). First, polyethylene glycol-maleate significantly enhances the adhesion with electrode active materials through copolymerization modification, especially in combination with high specific surface area materials (such as silicon, lithium cobalt oxide, etc.), which can effectively reduce the shedding and peeling of active materials during charging and discharging, thereby improving the cycle stability and capacity retention of the battery. However, PTFE has poor adhesion due to the presence of fluorine elements in its molecular structure, and usually requires a large amount of conductive agent to improve the conductivity, and the bonding effect is limited. Secondly, polyethylene glycol-maleate has good flexibility, especially after copolymerization modification, the modification of its molecular chain enhances the crack resistance of the electrode, can effectively alleviate the volume expansion and contraction during charging and discharging, avoid cracking and peeling of the electrode film, and extend the cycle life of the battery. However, the brittleness of PTFE makes it easy to crack when the volume of the electrode material changes, resulting in a decrease in battery performance.
[0035] In terms of conductivity, polyethylene glycol-maleate significantly improves its conductivity after copolymerization modification by introducing conductive monomers, which can reduce dependence on external conductive agents (such as carbon black, carbon nanotubes, etc.), reduce material costs and improve battery charging and discharging efficiency. In contrast, PTFE, as an electrical insulator, is not conductive and must rely on a large amount of conductive agents, which not only increases material costs, but may also affect the overall conductivity of the battery. Polyethylene glycol-maleate also has a low processing temperature and good processing adaptability. Electrodes can be directly prepared through a dry process, which simplifies the production process, reduces energy consumption, and reduces the need for high-temperature and high-pressure equipment, thereby reducing production costs and equipment maintenance costs. However, the processing technology of PTFE is complicated and needs to be carried out under high temperature and high pressure conditions. It has high equipment requirements and high energy consumption. In addition, due to its high friction coefficient, equipment wear is also serious.
[0036] From an environmental perspective, polyethylene glycol-maleate production requires almost no organic solvents or only uses a small amount of solvents. In contrast, the production and processing of PTFE usually requires the use of organic solvents, causing environmental pollution and increasing the cost of solvent recovery and treatment. DETAILED DESCRIPTION
[0037] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments may be combined with each other. The present invention will be further described in detail below in conjunction with specific embodiments.
[0038] The novel dry electrode binder of the embodiment of the present invention comprises polyethylene glycol-maleate. The preparation method thereof comprises:
[0039] Dissolution step: Take appropriate amounts of polyethylene glycol and maleic anhydride in molar ratio, and then add a solvent to completely dissolve the polyethylene glycol and maleic anhydride to obtain a uniform solution;
[0040] Esterification reaction steps: adding an appropriate amount of catalyst and stirring evenly to carry out esterification reaction, and adding an appropriate amount of dehydrating agent to absorb the water generated by the esterification reaction;
[0041] Solvent evaporation and concentration step: removing the reaction solvent to obtain a concentrated product;
[0042] Purification step: The concentrated product is subjected to solvent recrystallization to obtain pure polyethylene glycol-maleate, and then filtered, separated, and dried to obtain pure polyethylene glycol-maleate as a novel dry electrode binder.
[0043] Polyethylene glycol-maleate is a copolymer obtained by the reaction of polyethylene glycol (PEG) and maleic anhydride. It has good bonding properties, processability and low melting point, and can form a tight bond with electrode materials through a dry process at room temperature. Its molecules contain abundant hydrophilic and polar groups (such as carboxyl and ether groups), which can form strong chemical and physical interactions with active materials, enhance the bonding force of electrode materials, and reduce performance degradation caused by shedding or peeling of active materials. In addition, polyethylene glycol-maleate has good flexibility, which can effectively improve the mechanical strength and crack resistance of the electrode and extend the cycle life of the battery.
[0044] The novel dry electrode binder of the embodiment of the present invention includes polyethylene glycol-maleate-polypyrrole copolymer. The embodiment of the present invention further optimizes its performance through copolymerization modification to overcome the limitations of existing polytetrafluoroethylene (PTFE) as a dry electrode binder, thereby improving the preparation process of battery electrodes and the performance of batteries. The preparation method includes:
[0045] Dissolution step: Take appropriate amounts of polyethylene glycol and maleic anhydride in molar ratio, and then add a solvent to completely dissolve the polyethylene glycol and maleic anhydride to obtain a uniform solution;
[0046] Esterification reaction steps: adding an appropriate amount of catalyst and stirring evenly to carry out esterification reaction, and adding an appropriate amount of dehydrating agent to absorb the water generated by the esterification reaction;
[0047] Solvent evaporation and concentration step: removing the reaction solvent to obtain a concentrated product;
[0048] Purification step: the concentrated product is subjected to solvent recrystallization to obtain polyethylene glycol-maleate;
[0049] A polymerization reaction step: mixing polyethylene glycol-maleate with pyrrole to obtain a mixed solution;
[0050] Add ammonium persulfate solution dropwise to allow ammonium persulfate to gradually polymerize with pyrrole, and collect the resulting precipitate;
[0051] The unreacted pyrrole monomer and residual ammonium persulfate are removed by washing, and the polyethylene glycol-maleate-polypyrrole copolymer is obtained by drying to serve as a novel dry electrode binder.
[0052] Traditional PTFE, as a dry electrode binder, requires high temperature and high pressure during processing, resulting in complex production processes and high energy consumption; at the same time, due to the low flexibility and poor bonding properties of PTFE, it is easy to cause cracks in the electrode or the active material to fall off during use, affecting the cycle life and capacity retention of the battery. In addition, due to the electrical insulation of PTFE, a large amount of additional conductive agents are required, which further increases the cost and complexity of battery production. In order to further improve the performance of PEG-MA as a dry electrode binder, the present invention optimizes its structure through copolymerization modification. By copolymerizing with monomers having functional groups, the molecular structure of polyethylene glycol-maleate can be further adjusted to achieve higher bonding strength, good thermal stability and better conductivity. Copolymerization modification can also effectively improve the temperature resistance and corrosion resistance of polyethylene glycol-maleate, so that it maintains good performance under different environmental conditions, thereby effectively improving the performance of the battery, reducing production costs, and promoting the innovation and optimization of lithium battery manufacturing processes.
[0053] Materials required for preparing the novel dry electrode binder of the present invention:
[0054] Polyethylene glycol (H-(C2H4O) n -OH, PEG): The molecular weight can be selected from 1000 to 20000 to ensure high purity products;
[0055] Maleic anhydride (C2H2(CO)2O, MA): high purity product;
[0056] Catalyst: p-toluenesulfonic acid (PTSA) or other acid catalysts;
[0057] Solvent: anhydrous xylene or dichloromethane;
[0058] Others: Nitrogen (used to protect the reaction environment).
[0059] The preparation process is:
[0060] 1. Raw material preparation
[0061] PEG: Take PEG of the required molecular weight, weigh it and dry it in a vacuum oven at 60°C for several hours to remove adsorbed moisture.
[0062] Maleic Anhydride: Dry to ensure it is pure and free of moisture, dry in a vacuum desiccator for several hours.
[0063] 2. Dissolution Step
[0064] Add appropriate amount of PEG and maleic anhydride to the reaction flask in molar ratio. Add solvent anhydrous xylene, and place the reaction flask in a water bath or oil bath, and heat to 100-130°C to completely dissolve PEG and maleic anhydride to form a uniform solution.
[0065] 3. Esterification reaction steps
[0066] Add an appropriate amount of p-toluenesulfonic acid (PTSA) as a catalyst and stir evenly. The amount of catalyst used is generally 0.5-1% of the total mass of the reactants. Keep the temperature at 100-130℃ and continue stirring for 4-6 hours. A small amount of water will be produced during the esterification reaction.
[0067] Add an appropriate amount of anhydrous sodium sulfate or anhydrous calcium chloride as a dehydrating agent to absorb the water generated by the reaction to prevent the water from affecting the efficiency of the esterification reaction.
[0068] 5. Solvent evaporation and concentration steps
[0069] The reaction solvent was removed using a rotary evaporator at 40–50 °C to obtain a semi-solid crude product. To remove the residual solvent, the product was dried in a vacuum oven at low temperature to ensure that thermal decomposition was not induced.
[0070] 6. Purification Steps
[0071] The concentrated product is recrystallized from a solvent (e.g., ethanol or a dichloromethane / ethanol mixed solvent) to obtain pure polyethylene glycol-maleate. The crystal product is separated by filtration and dried in a vacuum drying oven to obtain pure polyethylene glycol-maleate powder.
[0072] The process of esterification of PEG and maleic anhydride to form polyethylene glycol-maleate mainly involves the following reaction formula:
[0073] The structural formula of PEG and maleic anhydride esterification:
[0074] .
[0075] Chemical reaction equation for the esterification reaction of PEG and maleic anhydride:
[0076] .
[0077] Purified polyethylene glycol-maleate product can be obtained through the above operation. The purified polyethylene glycol-maleate is chemically modified, and a copolymer of polyethylene glycol-maleate and pyrrole is prepared by a chemical oxidative polymerization method using ammonium persulfate (APS) as an oxidant.
[0078] The preparation of the copolymer involves the use of APS as an oxidant to initiate the oxidative polymerization of pyrrole, generating conductive polypyrrole (PPy) chains that are simultaneously bound to the active groups in PEG-maleate.
[0079] Raw materials preparation:
[0080] Select polyethylene glycol-maleate of appropriate molecular weight, high purity pyrrole reagent (C4H5N), and oxidant ammonium persulfate (APS, (NH4)2S2O8).
[0081] Polymerization reaction:
[0082] Pour the mixed solution of PEG-maleate and pyrrole into a three-necked flask, connect a condenser and a dropping funnel. Place the three-necked flask in an ice bath and keep the reaction temperature at 0℃-5℃. This will inhibit the over-polymerization of pyrrole and the occurrence of side reactions. Connect a magnetic stirrer and keep stirring at a medium speed to ensure that the mixture is uniform.
[0083] The prepared APS solution is slowly added to the mixed solution in the three-necked flask through a dropping funnel. The dropping time is controlled within 10-20 minutes to ensure that APS gradually reacts with pyrrole and avoid excessive local reaction. As the addition proceeds, the color of the solution gradually changes from colorless to dark green or black, pyrrole is oxidized, and polymerization initiated by free radicals occurs.
[0084] After the addition is completed, continue stirring at ice bath temperature (0℃-5℃) for 1-2 hours to inhibit the occurrence of side reactions and allow the polymerization reaction to proceed fully. Then remove the ice bath, allow the reaction system to gradually rise to room temperature, and continue stirring for 3-4 hours. At this time, the dark suspension gradually becomes thick, and the generated polypyrrole precipitate begins to form.
[0085] After the reaction is completed, the reaction system is cooled to room temperature. The generated dark precipitate is collected by filtering with filter paper. The collected precipitate is placed in a beaker and repeatedly washed with a large amount of deionized water until the filtrate is neutral. Then, anhydrous ethanol is used for further washing to remove unreacted pyrrole monomer and residual ammonium persulfate.
[0086] After washing, the precipitate is placed in a vacuum dryer and dried at 40-60° C. for 12-24 hours until the product is completely dry and has a constant mass, and finally a black powdery PEG-maleate-polypyrrole copolymer is obtained.
[0087] During the polymerization process, pyrrole is oxidized to a radical cation:
[0088] .
[0089] The pyrrole radical cation forms a long chain of polypyrrole PPy through free radical addition:
[0090] .
[0091] Copolymerization of polyethylene glycol-maleate:
[0092] .
[0093] The double bond part in PEG-maleate will react with the free radicals in the polypyrrole chain to form a copolymer structure and finally generate a copolymer. PEG is combined with polypyrrole through its terminal double bond. The chemical formula of polyethylene glycol-maleate and polypyrrole PEG-PPy is:
[0094] . Example 1
[0095] First, weigh polyethylene glycol (PEG-1000) with a molecular weight of 1000 and dry it in a vacuum oven at 60°C for 3 hours to remove the adsorbed moisture. Take an appropriate amount of maleic anhydride and dry it in a vacuum dryer for 1 hour. Add the dried PEG and maleic anhydride to the reaction flask in a molar ratio of 1:1, add dichloromethane as a solvent, place the reaction flask in a water bath or oil bath and heat it to 100°C to completely dissolve PEG and maleic anhydride to form a uniform solution. Then, add an appropriate amount of p-toluenesulfonic acid (PTSA) as a catalyst, and the amount of the catalyst is 0.5% of the total mass of the reactants. Keep the temperature at 100°C, stir for 4 hours to carry out the esterification reaction, and add an appropriate amount of anhydrous sodium sulfate as a dehydrating agent to absorb the moisture generated by the reaction to prevent moisture from affecting the efficiency of the esterification reaction. Monitor the progress of the reaction by thin layer chromatography (TLC) to observe the formation of maleic esters and determine the degree of completion of the reaction.
[0096] After the reaction is completed, a small amount of dilute sodium hydroxide solution is added to neutralize the residual acid catalyst in the system. The reaction system is washed with distilled water several times to remove the reaction by-products and residual acid. Then, the reaction solvent (dichloromethane) is removed at 40°C using a rotary evaporator to obtain a semi-solid crude product. In order to remove the residual solvent, the product is dried at low temperature in a vacuum oven to ensure that no thermal decomposition is caused, and a crude product of PEG-maleate is obtained. The crude product is dissolved in an appropriate amount of dichloromethane, and then an appropriate amount of pyrrole monomer is added to make the molar ratio of PEG-maleate to pyrrole be 1:2. Ammonium persulfate (APS) is added as an oxidant to initiate the polymerization of pyrrole. The reaction system is placed in an ice bath and cooled to 0°C to prevent the reaction from being too violent. Slowly add the APS solution to ensure uniform reaction. After stirring at low temperature for 1 hour, remove the ice bath and continue stirring at room temperature for 3 hours to ensure that PEG and pyrrole are fully copolymerized.
[0097] The copolymer precipitate is collected by filtration and repeatedly washed with deionized water and anhydrous ethanol to remove unreacted pyrrole monomer and by-products. After washing, the solvent is removed using a rotary evaporator to obtain a crude PEG-PPy copolymer. For further purification, the crude product is dissolved in a mixed solvent of dichloromethane and ethanol and solvent recrystallized to obtain pure PEG-PPy copolymer crystals. The crystals are separated by filtration and placed in a vacuum drying oven to obtain the final PEG-PPy copolymer powder.
[0098] The purified PEG-PPy copolymer powder is used to prepare the dry-process positive electrode of lithium-ion batteries. Weigh 90wt% of lithium iron phosphate (LiFePO4) as the active material, 5wt% of PEG-PPy copolymer powder as the binder, and 5wt% of conductive carbon black as the conductive agent. Add these materials to a high-speed mixer and mix them thoroughly to ensure that the binder and conductive carbon black are evenly distributed between the active material particles. The mixed dry powder material is evenly pressed into an electrode film with a thickness of 100 microns.
[0099] After the electrode membrane was prepared, volume resistance test and bonding strength test were performed to evaluate the performance of PEG-PPy copolymer as a binder. Example 2
[0100] First, weigh polyethylene glycol (PEG-5000) with a molecular weight of 5000 and dry it in a vacuum oven at 60°C for 3 hours to remove the adsorbed moisture. Take an appropriate amount of maleic anhydride and dry it in a vacuum dryer for 1 hour. Add the dried PEG and maleic anhydride to the reaction flask at a molar ratio of 2:3, add dichloromethane as a solvent, place the reaction flask in a water bath or oil bath and heat to 100°C to completely dissolve PEG and maleic anhydride to form a uniform solution. Then, add an appropriate amount of p-toluenesulfonic acid (PTSA) as a catalyst, and the amount of the catalyst is 0.5% of the total mass of the reactants. Keep the temperature at 100°C, stir for 4 hours to carry out the esterification reaction, and add an appropriate amount of anhydrous sodium sulfate as a dehydrating agent to absorb the moisture generated by the reaction to prevent moisture from affecting the efficiency of the esterification reaction.
[0101] After the reaction is completed, a small amount of dilute sodium hydroxide solution is added to neutralize the residual acid catalyst in the system. Then, the reaction solvent (dichloromethane) is removed at 40°C using a rotary evaporator. In order to remove the residual solvent, the product is dried at low temperature in a vacuum oven to ensure that no thermal decomposition is caused, and a crude product of PEG-maleate is obtained. The crude product is dissolved in an appropriate amount of dichloromethane, and then an appropriate amount of pyrrole monomer is added to make the molar ratio of PEG-maleate to pyrrole 1:1. Ammonium persulfate (APS) is added as an oxidant to initiate the polymerization of pyrrole. The reaction system is placed in an ice bath and cooled to 0°C to prevent the reaction from being too violent. The APS solution is slowly added to ensure uniform reaction. After stirring at low temperature for 2 hours, the ice bath is removed and stirring is continued at room temperature for 3 hours to ensure that PEG and pyrrole are fully copolymerized.
[0102] The purified PEG-PPy copolymer powder is used to prepare the dry-process positive electrode of lithium-ion batteries. 90wt% of lithium iron phosphate (LiFePO4) is weighed as the active material, 5wt% of PEG-PPy copolymer powder is used as the binder, and 5wt% of conductive carbon black is used as the conductive agent. The mixed dry powder material is evenly pressed into an electrode film with a thickness of 100 microns. After the electrode film is prepared, the volume resistance test and bonding strength test are performed to evaluate the performance of the PEG-PPy copolymer as a binder. Example 3
[0103] First, weigh polyethylene glycol (PEG-10000) with a molecular weight of 10,000 and dry it in a vacuum oven at 60°C for 3 hours to remove the adsorbed moisture. Take an appropriate amount of maleic anhydride and dry it in a vacuum dryer for 1 hour. Add the dried PEG and maleic anhydride to the reaction flask in a molar ratio of 1:1, add dichloromethane as a solvent, place the reaction flask in a water bath or oil bath and heat to 110°C to completely dissolve PEG and maleic anhydride to form a uniform solution. Then, add an appropriate amount of p-toluenesulfonic acid (PTSA) as a catalyst, and the amount of the catalyst is 0.5% of the total mass of the reactants. Keep the temperature at 110°C, stir for 4 hours to carry out the esterification reaction, and add an appropriate amount of anhydrous sodium sulfate as a dehydrating agent to absorb the moisture generated by the reaction to prevent moisture from affecting the efficiency of the esterification reaction.
[0104] After the reaction is completed, a small amount of dilute sodium hydroxide solution is added to neutralize the residual acid catalyst in the system. Then, the reaction solvent (dichloromethane) is removed at 40°C using a rotary evaporator. In order to remove the residual solvent, the product is dried at low temperature in a vacuum oven to ensure that no thermal decomposition is caused, and a crude product of PEG-maleate is obtained. The crude product is dissolved in an appropriate amount of dichloromethane, and then an appropriate amount of pyrrole monomer is added to make the molar ratio of PEG-maleate to pyrrole 1:1. Ammonium persulfate (APS) is added as an oxidant to initiate the polymerization of pyrrole. The reaction system is placed in an ice bath and cooled to 0°C to prevent the reaction from being too violent. The APS solution is slowly added to ensure uniform reaction. After stirring at low temperature for 3 hours, the ice bath is removed and stirring is continued at room temperature for 3 hours to ensure that PEG and pyrrole are fully copolymerized.
[0105] The purified PEG-PPy copolymer powder is used to prepare the dry-process positive electrode of lithium-ion batteries. 90wt% of lithium iron phosphate (LiFePO4) is weighed as the active material, 5wt% of PEG-PPy copolymer powder is used as the binder, and 5wt% of conductive carbon black is used as the conductive agent. The mixed dry powder material is evenly pressed into an electrode film with a thickness of 100 microns. After the electrode film is prepared, the volume resistance test and bonding strength test are performed to evaluate the performance of the PEG-PPy copolymer as a binder. Example 4
[0106] First, weigh polyethylene glycol (PEG-20000) with a molecular weight of 20,000 and dry it in a vacuum oven at 60°C for 3 hours to remove the adsorbed moisture. Take an appropriate amount of maleic anhydride and dry it in a vacuum dryer for 1 hour. Add the dried PEG and maleic anhydride to the reaction flask in a molar ratio of 1:1, add dichloromethane as a solvent, place the reaction flask in a water bath or oil bath and heat to 105°C to completely dissolve PEG and maleic anhydride to form a uniform solution. Then, add an appropriate amount of p-toluenesulfonic acid (PTSA) as a catalyst, and the amount of the catalyst is 0.5% of the total mass of the reactants. Keep the temperature at 105°C, stir for 4 hours to carry out the esterification reaction, and add an appropriate amount of anhydrous sodium sulfate as a dehydrating agent to absorb the moisture generated by the reaction to prevent moisture from affecting the efficiency of the esterification reaction.
[0107] After the reaction is completed, a small amount of dilute sodium hydroxide solution is added to neutralize the residual acid catalyst in the system. Then, the reaction solvent (dichloromethane) is removed at 40°C using a rotary evaporator. In order to remove the residual solvent, the product is dried at low temperature in a vacuum oven to ensure that no thermal decomposition is caused, and a crude product of PEG-maleate is obtained. The crude product is dissolved in an appropriate amount of dichloromethane, and then an appropriate amount of pyrrole monomer is added to make the molar ratio of PEG-maleate to pyrrole 2:3. Ammonium persulfate (APS) is added as an oxidant to initiate the polymerization of pyrrole. The reaction system is placed in an ice bath and cooled to 0°C to prevent the reaction from being too violent. APS solution is slowly added to ensure uniform reaction. After stirring at low temperature for 3 hours, the ice bath is removed and stirring is continued at room temperature for 3 hours to ensure that PEG and pyrrole are fully copolymerized.
[0108] The purified PEG-PPy copolymer powder is used to prepare the dry-process positive electrode of lithium-ion batteries. 90wt% of lithium iron phosphate (LiFePO4) is weighed as the active material, 5wt% of PEG-PPy copolymer powder is used as the binder, and 5wt% of conductive carbon black is used as the conductive agent. The mixed dry powder material is evenly pressed into an electrode film with a thickness of 100 microns. After the electrode film is prepared, the volume resistance test and bonding strength test are performed to evaluate the performance of the PEG-PPy copolymer as a binder.
[0109] Comparative Example 1
[0110] Weigh PEG and maleic anhydride with a molecular weight of 5000, add them to the reaction flask in a 1:1 molar ratio, use dichloromethane as a solvent, and heat in a 100°C water bath until completely dissolved. Add 0.5% PTSA as a catalyst, stir the reaction for 4 hours, add anhydrous sodium sulfate to remove moisture, neutralize with dilute sodium hydroxide and wash with water several times. Rotary evaporation removes the solvent to obtain polyethylene glycol-maleate powder without pyrrole copolymerization. Mix 90wt% lithium iron phosphate, 5wt% uncopolymerized polyethylene glycol-maleate and 5wt% conductive carbon black and press into an electrode film with a thickness of 100 microns. Perform volume resistance test and bonding strength test.
[0111] Comparative Example 2
[0112] PTFE powder with a molecular weight of 5000 was selected, 90wt% lithium iron phosphate, 5wt% PTFE powder and 5wt% conductive carbon black were mixed, and pressed into an electrode film with a thickness of 100 microns. Volume resistance test and bonding strength test were carried out.
[0113] The resistance test results are shown in Table 1, and the bonding strength test results are shown in Table 2.
[0114]
[0115]
[0116] The dry electrode plate of the present invention includes polyethylene glycol-maleate and / or polyethylene glycol-maleate-polypyrrole copolymer, that is, polyethylene glycol-maleate and / or polyethylene glycol-maleate-polypyrrole copolymer is used to replace polytetrafluoroethylene (PTFE) as a binder during the preparation of the dry electrode plate. Pyrrole is oxidized into free radical cations under the action of ammonium persulfate, and then free radical polymerization occurs to form a conductive polypyrrole chain, which is covalently bonded to PEG-maleate. After modification, it is used as a dry electrode binder with excellent conductive properties.
[0117] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A novel dry electrode binder, characterized in that: Including polyethylene glycol-maleate-polypyrrole copolymer, the chemical formula of polyethylene glycol-maleate-polypyrrole copolymer is: ; Wherein, m and n are both positive integers.
2. A method for preparing a novel dry electrode binder as claimed in claim 1, characterized in that: include: Dissolution step: Take appropriate amounts of polyethylene glycol and maleic anhydride in molar ratio, and then add a solvent to completely dissolve the polyethylene glycol and maleic anhydride to obtain a uniform solution; Esterification reaction steps: adding an appropriate amount of catalyst and stirring evenly to carry out esterification reaction, and adding an appropriate amount of dehydrating agent to absorb the water generated by the esterification reaction; Solvent evaporation and concentration step: removing the reaction solvent to obtain a concentrated product; Purification step: the concentrated product is subjected to solvent recrystallization to obtain polyethylene glycol-maleate; A polymerization reaction step: mixing polyethylene glycol-maleate with pyrrole to obtain a mixed solution; Add ammonium persulfate solution dropwise to allow ammonium persulfate to gradually polymerize with pyrrole, and collect the resulting precipitate; The unreacted pyrrole monomer and residual ammonium persulfate are removed by washing, and the polyethylene glycol-maleate-polypyrrole copolymer is obtained by drying to serve as a novel dry electrode binder.
3. The method for preparing the novel dry electrode binder according to claim 2, characterized in that: In the polymerization step, the filtrate is first washed with deionized water until the filtrate is neutral; then washed with anhydrous ethanol.
4. The method for preparing the novel dry electrode binder according to claim 2, characterized in that: In the polymerization step, the temperature is maintained at 0°C-5°C during the mixing and polymerization process.
5. The method for preparing the novel dry electrode binder according to claim 2, characterized in that: In the esterification step, the catalyst added is toluenesulfonic acid.
6. A dry electrode plate, characterized in that: The invention comprises a polyethylene glycol-maleate-polypyrrole copolymer, wherein the chemical formula of the polyethylene glycol-maleate-polypyrrole copolymer is: ; Wherein, m and n are both positive integers.
Citation Information
Patent Citations
Adhesive sheet and use thereof
CN113382860A
Cited By
Organosilane-polyethylene glycol conductive additive as well as preparation method and application thereof
CN121181878A